2012
DOI: 10.1371/journal.pone.0035046
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cytoskeleton Dynamics Modulates Non-Viral Gene Delivery through RhoGTPases

Abstract: Although it is well accepted that the constituents of the cellular microenvironment modulate a myriad of cellular processes, including cell morphology, cytoskeletal dynamics and uptake pathways, the underlying mechanism of how these pathways influence non-viral gene transfer have not been studied. Transgene expression is increased on fibronectin (Fn) coated surfaces as a consequence of increased proliferation, cell spreading and active engagement of clathrin endocytosis pathway. RhoGTPases mediate the crosstal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…One potential explanation of the altered transfection is that a similar mechanism may be at play as in a recent study showing that activation of regulators of G‐protein signaling (RGSs) prevent cyclic adenosine monophosphate and protein kinase A activity , and protein kinase A has been recently shown to modulate intracellular routing of polyplexes . Another potential mechanism of altered transfection is that RGS1 is a GAP that would alter cellular cytoskeleton dynamics via RhoGTPase signal transduction and therefore alter internalization and intracellular processing of polyplexes . In either event, altering the expression level of RGS1 can alter nonviral transfection possibly via G‐coupled signal transduction (GTPases Rho, Rac and CDC42) ending in processes known to affect transfection, such as endocytosis , cell spreading, migration, stress fibers, focal adhesion and cell motility (Figure ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…One potential explanation of the altered transfection is that a similar mechanism may be at play as in a recent study showing that activation of regulators of G‐protein signaling (RGSs) prevent cyclic adenosine monophosphate and protein kinase A activity , and protein kinase A has been recently shown to modulate intracellular routing of polyplexes . Another potential mechanism of altered transfection is that RGS1 is a GAP that would alter cellular cytoskeleton dynamics via RhoGTPase signal transduction and therefore alter internalization and intracellular processing of polyplexes . In either event, altering the expression level of RGS1 can alter nonviral transfection possibly via G‐coupled signal transduction (GTPases Rho, Rac and CDC42) ending in processes known to affect transfection, such as endocytosis , cell spreading, migration, stress fibers, focal adhesion and cell motility (Figure ).…”
Section: Discussionmentioning
confidence: 93%
“…Another potential mechanism of altered transfection is that RGS1 is a GAP that would alter cellular cytoskeleton dynamics via RhoGTPase signal transduction and therefore alter internalization and intracellular processing of polyplexes . In either event, altering the expression level of RGS1 can alter nonviral transfection possibly via G‐coupled signal transduction (GTPases Rho, Rac and CDC42) ending in processes known to affect transfection, such as endocytosis , cell spreading, migration, stress fibers, focal adhesion and cell motility (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the cell itself, cell proliferation, cell area, internalization, intracellular trafficking and integrin expression modulate gene transfer efficiency. Furthermore, for cells plated in 2-D on ECM proteins, the gene transfer is modulated by internalization pathways, cytoskeletal dynamics and RhoGTPases mediated signalling 16, 17 . Most of the studies have focused on studying the parameters influencing non-viral gene delivery in cells plated in 2-D, while little is known about 3-D.…”
Section: Discussionmentioning
confidence: 99%
“…Such methods often involve incubating a porous scaffold in a solution rich in condensed DNA before washing the scaffold to remove unbound particles [142][143][144][145] or hydrating a lyophilized hydrogel in a condensed DNA solution. [146][147][148][149] Via the first method, Saul et al 138 reported a maximal loading capacity of approximately 44 mg complexed DNA per 8-mm diameter by 2-mm thickness porous fibrin gel. 142 The load amount varies with the DNA:PEI ratio used to form the polyplexes, which controls the surface charge of the polyplexes.…”
Section: Condensed Plasmid Using Cationic Polymer-and Lipid-based Genementioning
confidence: 99%